Private Regulatory Fragmentation as Public Policy: Governing Canada’s Mining Industry - Marques, José Carlos (Journal of business ethics, 2016)
This paper addresses recent calls to study the role of the state in private regulation. Integrating current scholarship on the state as a catalyst of private regulatory regimes with prior literature on regulatory failure and self-regulation, it identifies and problematizes unsettled assumptions used as a starting point by this growing body of research. The case study traces the evolution of public debates and the interaction of different regulatory initiatives dealing with corporate social responsibility (CSR) issues in Canada’s mining industry. Findings reveal the conditions under which the state is more likely to encourage firm-level, fragmented initiatives than facilitate and promote industry-wide regulatory strengthening and consolidation. I discuss the need for greater analytical precision regarding the variation in regulatory policy preferences across time and branches of government and the interaction between public and private regulatory initiatives. The conclusion outlines suggested areas for future research as well as the likely outcome of Canada’s current CSR policy framework.